2022
DOI: 10.3389/fnagi.2021.789785
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Functional Connectivity in de novo Parkinson’s Disease Patients With Depression

Abstract: BackgroundDepression is one of the most prevalent and disturbing non-motor symptoms in Parkinson’s disease (PD), with few dynamic functional connectivity (dFC) features measured in previous studies. Our aim was to investigate the alterations of the dynamics in de novo patients with PD with depression (dPD).MethodsWe performed dFC analysis on the data of resting-state functional MRI from 21 de novo dPD, 34 de novo patients with PD without depression (ndPD), and 43 healthy controls (HCs). Group independent compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…For example, Parkinson’s and associated diseases (i.e. Parkinson’s disease mild cognitive impairment – PDM; Parkinson’s disease dementia - PDD) are characterized by altered temporal properties in dynamic connectivity (Díez-Cirarda et al, 2018; Fiorenzato et al, 2019; Kim et al, 2017; Xu et al, 2021). Previous work found decreased mean dwell time in segregated within-network connectivity states and increased brain state transitions in PD and PDM compared to matched control participants (Díez-Cirarda et al, 2018; Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Parkinson’s and associated diseases (i.e. Parkinson’s disease mild cognitive impairment – PDM; Parkinson’s disease dementia - PDD) are characterized by altered temporal properties in dynamic connectivity (Díez-Cirarda et al, 2018; Fiorenzato et al, 2019; Kim et al, 2017; Xu et al, 2021). Previous work found decreased mean dwell time in segregated within-network connectivity states and increased brain state transitions in PD and PDM compared to matched control participants (Díez-Cirarda et al, 2018; Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we obtained the global and local efficiency at each sparsity threshold. We applied an area under the curve (AUC) approach to avoid specific threshold selection (Kim et al, 2017; Navalpotro-Gomez et al, 2020; Xu et al, 2021). Finally, as suggested by Kim et al (Kim et al, 2017), we calculated the variance of the global and local efficiency over time to examine dynamic graph properties differences of younger and older participants and compared these metrics using Wilcoxon rank-sum test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed abnormal temporal property of local neural activity in the visual, sensorimotor, and cognitive systems in PD, which was consistent with the previous studies. For example, the previous fMRI studies that calculated the variability of brain signal across time found abnormal variance in visual [47][48][49] , sensorimotor 47,50 , and frontal 51,52 regions in PD. Some studies also found that the symptom severity of PD significantly correlated with such abnormal variability in the visual and sensorimotor regions.…”
Section: Discussionmentioning
confidence: 99%
“…In de novo PD patients with depression, altered network connection involving the default mode network and cognitive executive network may contribute to depression (Xu et al 2022b ). Likewise, altered neural network connectivity within the ventral attention network in the left middle temporal cortex, the auditory and default mode networks may predict depression in de novo PD (Xu et al 2022a ).…”
Section: Dpd and Brain Circuit Disturbancesmentioning
confidence: 99%